LENGTH-WEIGHT RELATIONSHIP AND CONDITION FACTOR OF INVASIVE Penaeus monodon ALONG THE SOUTH COASTLINE OF NIGERIA - OKETOKI, T.O; ANSA, E. J; OGUNTADE, O.R; UKENYE, E.A; OMIDIJ, O. (Nigerian Journal of Fisheries, 2016)
The study of Length-weight relationship (LWR) of aquatic species is significant in fisheries biology because of their usefulness in estimating weight parallel to a given length. In this study, ten locations covering five coastal states vis à-vis Lagos Makoko (LM), Lagos Apapa (LA), Lagos Takwabay (LT), Lagos Tincan (LC), Lagos Folu (LF), Ondo Aiyetoro (AO), Bayelsa Brass (BB), Rivers Bonny (RB), Rivers Kaa (RK) Akwa Ibom Ibeno (AB) were used for the analysis of LWR and condition factor of the invasive tiger shrimps. A total of 400 samples were used. Sex dimorphism by size variation showed Females (South West: 24.4±2.7 cm; 143.2±29.3g , South-South: 24.0±2.5 cm;139.3±28.2g ) being significantly larger than males (South West: 19.0±4.02 cm; 96.8±35.1g , South-South: 19.7±3.26 cm;100.4±25.8g ) (P<0.01). Condition factor k was reported significantly higher in males (South west: 1.548± 0.6, South-South: 1.393±0.53) than females (South west: 0.974±0.17, South-south: 0.971±0.14) (P < 0.01). All Length-Weight relationships were positively correlated.